EXPLORING STUDENTS’ PERCEPTION TOWARD TEACHING LISTENING BY USING ENGLISH SONG AT LPBA NURUL JADID - Tolhairi, Roby (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
This study aims to explore students' perceptions of teaching listening using English songs at LPBA Nurul Jadid. The research utilizes a qualitative descriptive method, employing interviews and documentation as data collection techniques. Thirty-three students from LPBA Nurul Jadid were interviewed to gather data, which was subsequently analysed using qualitative descriptive methods, including data reduction, data presentation, inference and verification, and drawing conclusions. The interview results revealed that 88% of the students held a positive perception of learning to listen through English songs. According to the students, this approach sparked their interest, motivation, relaxation, and happiness in learning, resulting in improved listening skills and pronunciation of vocabulary. On the other hand, approximately 12% of the students maintained a neutral perception towards learning listening with English songs. This minority group preferred alternative media for their listening practice. Regarding the documentation, the researcher did not find any physical data. It was observed that after completing the listening tasks assigned by the teacher, the students promptly submitted their assignments, leaving no tangible evidence. However, the researcher did uncover specific song titles used by the teacher in the listening activities, namely "Sweet but Psycho" by Ava Max and "Lily" by Alan Walker.